Charge Transfer Between d-p States in Ti02 By Employing Compton Scattering Techniques - Mobammad, F.M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The com pton profiles for Ti02 have been measured using a SCi Am-241 compton spectrometer .A pellet of the oxide was prepared from a polycrystalline powder having a thickness of 1.54 mm ,about J 00000 counts have been accumulated at the compton peak .Theoreti cal compton profiles have been calculated for different ionic anangements using free atom compton profile for the core electrons.The theoretical and experimental results ahrce well for (Ti/4(0 .2 arrangement which support complete transfer of valence electrons from metal to oxygen ions, i.e., full ionic bonding in this oxide in agreement with available pbotoemission and other studies .